Organizing integrated care for older persons: strategies in Sweden during the past decade. Issue 1 (16th March 2015) - Berglund, Helene; Blomberg, Staffan; Dunér, Anna; Kjellgren, Karin
Abstract : Purpose: – The purpose of this paper is to describe and analyse ways of organizing integrated care for older persons in Sweden during the past decade. Design/methodology/approach: – The data consist of 62 cases of development work, described in official reports. A meta-analysis of cases was performed, including content analysis of each case. A theoretical framework comprising different forms of integration (co-ordination, contracting, co-operation and collaboration) was applied. Findings: – Co-operation was common and collaboration, including multiprofessional teamwork, was rare in the cases. Contracting can be questioned as being a form of integration, and the introduction of consumer choice models appeared problematic in inter-organization integration. Goals stated in the cases concerned steering and designing care, rather than outcome specifications for older persons. Explicit goals to improve integration in itself could imply that the organizations adapt to strong normative expectations in society. Trends over the decade comprised development of local health care systems, introduction of consumer choice models and contracting out. Research limitations/implications: – Most cases were projects, but others comprised evaluations of regular organization of integrated care. These evaluations were often written normatively, but constituted the conditions for practice and were important study contributions. Practical implications: – Guiding clinical practice to be aware of importance of setting follow-up goals. Social implications: – Awareness of the risk that special funds may impede sustainable strategies development. Originality/value: – A theoretical framework of forms of integration was applied to several different strategies, which had been carried out mostly in practice. The study contributes to understanding of how different strategies have been developed and applied to organize integrated care, and highlights some relationships between integration theory and practice.